2022
DOI: 10.3390/ijms23031108
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of JNK and p38 MAPK Signaling in Nasopharyngeal Carcinoma

Abstract: c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) family members integrate signals that affect proliferation, differentiation, survival, and migration in a cell context- and cell type-specific way. JNK and p38 MAPK activities are found upregulated in nasopharyngeal carcinoma (NPC). Studies have shown that activation of JNK and p38 MAPK signaling can promote NPC oncogenesis by mechanisms within the cancer cells and interactions with the tumor microenvironment. They regulate multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 151 publications
2
42
0
1
Order By: Relevance
“…ERKs are mainly related to cell proliferation and differentiation (Pashirzad et al, 2021; Sugiura et al, 2021). JNKs, by activating the intrinsic pathway, enables Bcl‐2 to participate in the release of pro‐apoptotic molecules, which leads to activation of caspases and ultimately cell apoptosis (Pua et al, 2022). P38MAPKs could regulate cell apoptosis by enhancing the expression of c‐Myc, phosphorylating p53, activating c‐Jun, among other functions (Pua et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ERKs are mainly related to cell proliferation and differentiation (Pashirzad et al, 2021; Sugiura et al, 2021). JNKs, by activating the intrinsic pathway, enables Bcl‐2 to participate in the release of pro‐apoptotic molecules, which leads to activation of caspases and ultimately cell apoptosis (Pua et al, 2022). P38MAPKs could regulate cell apoptosis by enhancing the expression of c‐Myc, phosphorylating p53, activating c‐Jun, among other functions (Pua et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…JNKs, by activating the intrinsic pathway, enables Bcl‐2 to participate in the release of pro‐apoptotic molecules, which leads to activation of caspases and ultimately cell apoptosis (Pua et al, 2022). P38MAPKs could regulate cell apoptosis by enhancing the expression of c‐Myc, phosphorylating p53, activating c‐Jun, among other functions (Pua et al, 2022). Metabolic pathways are always complicated and even a tiny little intervention can have dramatic effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK inhibitors for CRC treatment have also been introduced as clinical treatments [ 56 , 57 ]. However, emerging evidence has also shown a tumor suppressor role of JNK proteins [ 20 , 54 , 58 ]. The reason for the dual role of JNK or MAPK proteins may be different crossroads in the molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the functions of p38 MAPK in cancer have been widely investigated. Evidences have indicated that the stage of tumor development can strongly govern the function of p38 MAPK, with a low p38 MAPK activity generally favoring malignancy at early stages and p38 MAPK being highly activated at the advanced stages of tumorigenesis, involving migration to adjacent organs ( Martinez-Limon et al, 2020 ; Pua et al, 2022 ). In addition, the role of p38 MAPK in CSC regulation has been validated.…”
Section: Discussionmentioning
confidence: 99%